Retrieval Practice as Process in Self-Directed Learning: New Philosophical Directions for Self-Directed Learning - Daniel A. Parker; Kevin M. Roessger (Adult Education Research Conference, 2019)
We explain retrieval practice and its potential benefits for adult self-directed learners. Moreover, we argue functional contextualism as an alternative research philosophy to self-directed learning’s humanist assumptions.
Keywords: functional contextualism; adult learning strategies; SDL; learning sciences